1985
DOI: 10.1111/j.1445-5994.1985.tb04006.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Extra‐sellar Pituitary Tumours With Bromocriptine: Comparison of Prolactin Secreting and Non‐functioning Tumours Using Half‐field Visual Evoked Potentials and Computerised Tomography

Abstract: To determine whether prolactin secreting and non-functioning pituitary tumours respond differently in terms of shrinkage to bromocriptine, we prospectively studied ten consecutive patients (five with prolactinomas and five with non-functioning tumours) complicated by extra-sellar extensions. No patient had received prior radiotherapy or bromocriptine and the mean dose and duration of bromocriptine treatment were identical in the two groups of patients. Objective evidence of tumour shrinkage was provided by ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In NFA, as shown in Table 2, the cumulative evidence for tumour shrinkage after DA therapy is 27.6% (Johnston et al 1981, Wass et al 1982, Barrow et al 1984, Grossman et al 1985, Pullan et al 1985, Verde et al 1985, Zárate et al 1985, D'Emden & Harrison 1986, Bevan et al 1987, Klibanski et al 1988, García-Luna et al 1989, van Schaardenburg et al 1989, Abs et al 1991, Kwekkboom & Lamberts 1992, Van Tol et al 1992, Ferone et al 1998, Colao et al 2000b, Giusti et al 2000, Nobels et al 2000, Hofland & Lamberts 2001, Lohmann et al 2001, Pivonello et al 2004, Greenman et al 2005. When compared with that obtained with SSA (5%), the latter was significantly different (c 2 test, P!0.0001).…”
Section: Results Of Treatment With Damentioning
confidence: 99%
“…In NFA, as shown in Table 2, the cumulative evidence for tumour shrinkage after DA therapy is 27.6% (Johnston et al 1981, Wass et al 1982, Barrow et al 1984, Grossman et al 1985, Pullan et al 1985, Verde et al 1985, Zárate et al 1985, D'Emden & Harrison 1986, Bevan et al 1987, Klibanski et al 1988, García-Luna et al 1989, van Schaardenburg et al 1989, Abs et al 1991, Kwekkboom & Lamberts 1992, Van Tol et al 1992, Ferone et al 1998, Colao et al 2000b, Giusti et al 2000, Nobels et al 2000, Hofland & Lamberts 2001, Lohmann et al 2001, Pivonello et al 2004, Greenman et al 2005. When compared with that obtained with SSA (5%), the latter was significantly different (c 2 test, P!0.0001).…”
Section: Results Of Treatment With Damentioning
confidence: 99%
“…Repeat CT scans were not performed so it is not possible to assess whether visual improvement was accompanied by radiological improvement. However CT can only detect relatively large changes in tumour size, and visual field improvement without CT changes has been reported (Pullan et al, 1985) and is probably due to a small reduction of tumour volume not detected by CT.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in visual fields and acuity can be utilized as relatively sensitive indicators of small changes of tumour volume providing that destruction of optic fibres has not occurred. Visual evoked responses may also prove useful (Pullan et al, 1985). However the presence of visual field defects commonly precipitates neurosurgical intervention, preventing a trial of bromocriptine in this circumstance (Teasdale, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…1), this may have been due to a lack of sensitivity of this method since only a very small amount of tumor reduction can cause decompression. Pullan et al [24] have also reported a patient with a pituitary tumor who experienced im provement of a visual lesion without parallel changes in the tumor size on a CT scan. Another possibility for the visual improvement may have been a reduction in the size of the normal lactotroph cells, since such a phenom enon would induce a marginal decrease in the size of the contents of the pituitary fossa which, as a consequence, could allow for a transient decompression of the visual pathways [25].…”
Section: Discussionmentioning
confidence: 99%